2014
DOI: 10.3382/ps.2013-03182
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxy-4-methylselenobutanoic acid induces additional tissue selenium enrichment in broiler chickens compared with other selenium sources

Abstract: Two experiments were conducted in broiler chickens to compare the effect of different Se sources on Se tissue enrichment: sodium selenite (SS), seleno-yeast (SY), and a new organic Se source (SO) containing 2-hydroxy-4-methylselenobutanoic acid (HMSeBA) as an active substance. For each experiment, treatments differed only in source or dose of Se additive. Relative efficiency was compared by plasma and tissue [muscle (pectoralis major) and liver] total Se concentrations. The first experiment compared Se sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 37 publications
(79 reference statements)
4
45
0
Order By: Relevance
“…In a comparison of the effect of OH-SeMet with that of sodium selenite and Se-yeast, all three Se sources increased muscle Se compared with control chickens, with a significant (P<0.05) source effect in the order OH-SeMet>Se-yeast> sodium selenite and the effect of OH-SeMet being 1.5-fold stronger than that of Se-yeast (Briens et al, 2014). Selenium speciation in tissues indicates that muscle Se is exclusively present as SeMet or SeCys, indicating a full conversion of OH-SeMet to active Se species in the bird.…”
Section: Oh-semetmentioning
confidence: 97%
See 1 more Smart Citation
“…In a comparison of the effect of OH-SeMet with that of sodium selenite and Se-yeast, all three Se sources increased muscle Se compared with control chickens, with a significant (P<0.05) source effect in the order OH-SeMet>Se-yeast> sodium selenite and the effect of OH-SeMet being 1.5-fold stronger than that of Se-yeast (Briens et al, 2014). Selenium speciation in tissues indicates that muscle Se is exclusively present as SeMet or SeCys, indicating a full conversion of OH-SeMet to active Se species in the bird.…”
Section: Oh-semetmentioning
confidence: 97%
“…Recently, a new organic Se source, OH-SeMet (2-hydroxy-4-melhylselenobutanoic acid or HMSeBA), has been developed (Briens et al, , 2014. It is a precursor of SeMet and after its dietary consumption, OH-SeMet is easily converted into SeMet and metabolized in the same way as pure SeMet, including building Se reserves in muscles.…”
Section: Oh-semetmentioning
confidence: 99%
“…Two principal forms of Se are currently used: inorganic Se, such as sodium selenite (SS) or sodium selenite, and organic Se, such as selenium yeast (SY). Many previous studies have shown that SY, the most widely used organic Se feed supplementation, has higher bioavailability (Briens et al, 2014) and is associated with a larger increase in Se in milk (Givens et al, 2004) and blood (Walker et al, 2010) and a greater improvement in antioxidant status (Gong et al, 2014;Sun et al, 2017).…”
Section: Short Communicationmentioning
confidence: 99%
“…Hydroxy-selenomethionine (HMSeBA) contains the active compound 2-hydroxy-4-methylselenobutanoic acid. It was approved for use as a new source of organic Se in some countries in 2013 (EFSA, 2013), and several studies have been published regarding effects of HMSeBA supplementation on growth performance and Se concentration in monogastric animals (Briens et al, , 2014Jlali et al, 2013). In ruminants, our previous study showed that HMSeBA could replace SS in the diet of dairy cows because it was more effective at improving antioxidant status and Se concentrations in plasma and milk than SS (Sun et al, 2017).…”
Section: Short Communicationmentioning
confidence: 99%
“…Based on:Mahan and Parrett, 1996; Mahan et al, 1999; Mateo et al, 2007;Svoboda et al, 2009; Kawecka et al, 2013; Jlali et al, 2014. (b): Based on:Skřivan et al, 2008;Petrovic et al, 2010; Hu et al, 2012;Ryzner et al, 2013;Chen et al, 2013;Briens et al, 2014. (c): Based on: Juniper et al, 2011.…”
mentioning
confidence: 99%